Cardiac toxicity in breast cancer patients treated with dual HER2 blockade. Issue 9 (29th May 2013) - Valachis, Antonis; Nearchou, Andreas; Polyzos, Nikolaos P.; Lind, Pehr
<x xml:space="preserve">Abstract</x> Although dual HER2 blockade shows promising results in patients with HER2‐positive breast cancer it is unclear whether this treatment strategy increases the risk for cardiac adverse events. We conducted a meta‐analysis of randomized trials to investigate the risk of cardiac adverse events when a combination of anti‐HER2 therapies compared to anti‐HER2 monotherapy. We searched Medline, the Cochrane library, as well as the electronic abstract databases of the major international congresses' proceedings to identify randomized trials that evaluated the administration of anti‐HER2 monotherapy (lapatinib or trastuzumab or pertuzumab) versus anti‐HER2 combination (pertuzumab plus trastuzumab or trastuzumab plus lapatinib) therapy in breast cancer. The trials were considered eligible if the only systematic difference between the study arms was the type of anti‐HER2 therapy used. Study outcomes were the congestive heart failure (CHF) grade ≥3 and left ventricular ejection fraction (LVEF) decline <50% or more than 10% from baseline. Six trials were considered eligible. Overall incidence results for CHF in the combined anti‐HER2 therapy and the anti‐HER2 monotherapy were 0.88% (95% CI: 0.47–1.64%) and 1.49% (95% CI: 0.98–2.23%). The incidence of LVEF decline was 3.1% (95% CI: 2.2–4.4%) and 2.9% (95% CI: 2.1–4.1%), respectively. The OR of CHF between anti‐HER2 combination and monotherapy was 0.58 (95% CI: 0.26–1.27, p‐value= 0.17) while the OR of LVEF decline was 0.88 (95% CI: 0.53–1.48, p‐value= 0.64). This meta‐analysis provides evidence supporting comparable cardiac toxicity between anti‐HER2 combination therapy and anti‐HER2 monotherapy.